Symptoms and Immune Markers in Plasmodium/Dengue Virus Co-infection Compared with Mono-infection with Either in Peru. - Eric S Halsey; G Christian Baldeviano; Kimberly A Edgel; Stalin Vilcarromero; Moises Sihuincha; Andres G Lescano (Public Library of Science (PLoS), 2016)
Malaria and dengue are two of the most common vector-borne diseases in the world, but co-infection is rarely described, and immunologic comparisons of co-infection with mono-infection are lacking.We collected symptom histories and blood specimens from subjects in a febrile illness surveillance study conducted in Iquitos and Puerto Maldonado, Peru, between 2002-2011. Nineteen symptoms and 18 immune markers at presentation were compared among those with co-infection with Plasmodium/dengue virus (DENV), Plasmodium mono-infection, and DENV mono-infection. Seventeen subjects were identified as having Plasmodium/DENV co-infection and were retrospectively matched with 51 DENV mono-infected and 44 Plasmodium mono-infected subjects. Those with Plasmodium mono-infection had higher levels of IL-4, IL-6, IL-10, IL-12, IL-13, IL-17A, IFN-γ, and MIP1-α/CCL3 compared with DENV mono-infection or co-infection; those with Plasmodium mono-infection had more cough than those with DENV mono-infection. Subjects with DENV mono-infection had higher levels of TGF-β1 and more myalgia than those with Plasmodium mono-infection. No symptom was more common and no immune marker level was higher in the co-infected group, which had similar findings to the DENV mono-infected subjects.Compared with mono-infection with either pathogen, Plasmodium/DENV co-infection was not associated with worse disease and resembled DENV mono-infection in both symptom frequency and immune marker level.